Trends and level of control of hypertension among adults attending an ambulatory HIV clinic in Kampala, Uganda: a retrospective study. Issue 3 (24th November 2016) - Kalyesubula, Robert; Kayongo, Alex; Semitala, Fred Collins; Muhanguzi, Asaph; Katantazi, Nehemiah; Ayers, Dieter; Forrest, Jamie I; Mills, Edward J
Abstract : Background: With an ageing HIV-positive population, sub-Saharan Africa is now facing a dual epidemic of communicable and non-communicable diseases (NCDs). This study aimed to assess trends in the prevalence of hypertension and factors associated with hypertension, among adults attending an ambulatory HIV clinic in Kampala, Uganda. Methods: We conducted a retrospective chart review to identify patients with hypertension. We used a random number generator to select 400 patient charts from each year from 2009 to 2014. Blood pressure, age, body mass index (BMI), WHO disease stage and Karnofsky scores were extracted. Logistic regression was used to estimate the strength of the association between each of these factors and the presence of hypertension. Results: In total, 1996 charts were included in this analysis. The mean age of participants was 31 years and 1311/1996 (65.7%) were female. The overall prevalence of hypertension was 418/1996 (20.9%). This rose from 16.9% in 2009 to 32.3% in 2013. Of the patients with hypertension, 96/418 (23.0%) were receiving adequate treatment. Patients >50 years of age had 3.12 times the odds of hypertension compared with patients aged 20–29 years (95% CI 2.00 to 4.85). Men had 1.65 times the odds of hypertension compared with women (95% CI 1.34 to 2.03) and patients with a BMI of 35–39 kg/m 2 had 3.93 times the odds of hypertension compared with patients with a BMI <25 kg/m 2 . Conclusions: The prevalence of hypertension is rising in the Ugandan HIV-positive population. There remains inadequate management and control of hypertension in this group highlighting the need to better integrate NCD care within the HIV clinical settings.